Evaluation of the Islamic Boarding School Health Post Program (Poskestren) Based on the CIPP (Context, Input, Process, Product) Theory: A Scoping Review - Aldiella Ayu Prasetya Astuti; Rery Afianto; Renaldi Renaldi; Muthmainnah Muthmainnah; Muji Sulistyowati; Aprillia Nurhayati (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Indonesia hosts 39,551 Islamic boarding schools (pesantren) with approximately 4.9 million students, many of which experience limited access to health services. The Islamic Boarding School Health Post (Poskestren) program was designed to strengthen promotive and preventive health services in pesantren, yet systematic evaluation of its implementation remains limited. Objective: This study analyzes the implementation of the Poskestren program in Indonesia using the Context, Input, Process, and Product (CIPP) evaluation model. Methods: A scoping review was conducted using Google Scholar with the keyword “implementation of pesantren health post (Poskestren).” Inclusion criteria comprised full-text, open-access articles published between 2020 and 2025 that explicitly evaluated Poskestren. Six relevant articles met the criteria and were synthesized. Results: The Poskestren program demonstrates strategic relevance and potential benefits for student health; however, multiple implementation gaps persist. CIPP-based analysis and comparison with the Minister of Health Regulation No. 1 of 2013 indicate that standards are not fully achieved. Major constraints include inadequate health facilities, limited medical equipment, insufficient training and competency of health cadres, weak supervision mechanisms, and low student participation in health activities. Conclusion: Poskestren is a vital school-based health initiative, but its effectiveness depends on improved resource allocation, structured cadre capacity building, stronger coordination, and comprehensive monitoring and evaluation systems to improve health outcomes among pesantren students.